DETERMINING THE RANGE OF COMBINE HARVESTERS AND HEADERS FOR KAZAKHSTAN REGIONS - V. L. Astafyiev; V A Golikov (Сельскохозяйственные машины и технологии, 2018)
The fleet of combine harvesters in the Republic of Kazakhstan consists of 3-, 4-, 5- and 6-class harvesters, and 3- and 4- class harvesters make up for almost 82% of the fleet. According to the data provided by the Kazakhstan Ministry of Agriculture, 60% of grain harvesters have a lifespan of more than 10 years. (Research purpose) To determine the range of grain harvesters and headers for Kazakhstan regions in view of ongoing technical re-equipment. (Materials and methods) The range of grain harvesters should be determined according to the yield of harvested crops, the size of crop area on separate farms and in the region, the availability of machine operators as well as climatic conditions of the regions. (Results and discussions). The authors have analyzed the actual yield of grain crops in Kazakhstan regions, determined its possible expected level, and analyzed the number of machine operators required for available crop area, the number of small, medium and large-scale farms and climatic conditions during the harvest period in Kazakhstan regions. The efficiency of harvesters of different classes with headers of various operating width has been estimated taking into account the expected yield. Matching the obtained results to the yield data, organizational-and-economic and climatic conditions, and introducing appropriate limits, the authors have determined the range of grain harvesters for Kazakhstan regions. (Summary) It has been found that the harvesters of class 5, 6 and 4 are more effective under conditions of northern and central Kazakhstan regions provided they are equipped with wide-cut headers for direct harvesting. In southern, western and eastern Kazakhstan regions, where grain crops are cultivated on dry soils with an insufficient moisture content, combine harvesters of class 3 and 4 should be primarily used.